The Function and Expression of ATP-Binding Cassette Transporters Proteins in the Alzheimer's Disease - Aykac, Asli; Sehirli, Ahmet Özer (Global Medical Genetics, 2021)
Despite many years of research, radical treatment of Alzheimer's disease (AD) has still not been found. Amyloid-β (Aβ) peptide is known to play an important role in the pathogenesis of this disease. AD is characterized by three main changes occurring in the central nervous system: (1) Aβ plaque accumulation that prevents synaptic communication, (2) the accumulation of hyperphosphorylated tau proteins that inhibit the transport of molecules inside neurons, and (3) neuronal cell loss of the limbic system. Mechanisms leading to Aβ accumulation in AD are excessive Aβ production as a result of mutations in amyloid precursor protein or genes, and impairment of clearance of Aβ due to changes in Aβ aggregation properties and/or Aβ removal processes. Human ATP-binding cassette (ABC) transporters are expressed in astrocyte, microglia, neuron, brain capillary endothelial cell, choroid plexus, choroid plexus epithelial cell, and ventricular ependymal cell. ABC transporters have essential detoxification and neuroprotective roles in the brain. The expression and functional changes in ABC transporters contribute to the accumulation of Aβ peptide. In conclusion, the review was aimed to summarize and highlight accumulated evidence in the literature focusing on the changing functions of human ABC transporter members, in AD pathogenesis and progression.
Keywords: ABC transporters; Alzheimer's diseases; amyloid-β; P-glycoprotein; multidrug resistance protein 1